3D TUDE MOVIE SERIES â€œHANDBAN KEBERUNTUNGANâ€ - Agus Sutrisna, I Kadek; Crisnapati, Padma Nyoman; Gede Sunarya, I Made; Antara Kesiman, Made Windu (Universitas Pendidikan Ganesha, 2013)
3D animation movie titled